On Pre Rg-Continuous Functions in Topology - Mookanagoudar, Sujata; Navalagi, Govindappa (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2018)
In this paper we define and study the concept of pre-Rg-continuous functionsusing preopen sets due to Mashhour et.al (1982) and rg-open sets due to N . Palaniappan(1993). Also,we study the pre-g-regular spaces. Mathematics Subject Classification(2010) : 54A05, 54B05,54C08, 54D10.